Nomograms to Predict Endocrinological Deficiency in Patients With Surgically Treated Craniopharyngioma - Wu, Jie; Wu, Xiao; Yang, Le; Xie, ShenHao; Tang, Bin; Tong, ZhiGao; Wu, BoWen; Yang, YouQing; Ding, Han; Bao, YouYuan; Zhou, Lin; Hong, Tao (Frontiers in Oncology, 2022)
Objective Postoperative hypopituitarism associated with increased risks of premature mobility and mortality is often encountered in craniopharyngioma patients. The aim of our study is to construct nomograms related to injury types of the hypothalamus-pituitary axis (HPA) to predict hypopituitarism 1 year after surgery. Methods Craniopharyngioma patients undergoing initial endoscopic endonasal surgery between December 2012 and March 2021 in our center were retrospectively reviewed and injury types of the HPA were categorized according to intraoperative endoscopic observation. Included patients were randomly divided into a training group and a validation group. Nomograms were established based on the results of multivariate logistic analysis. The predictive performance of the nomograms was evaluated in the training and validation groups. Results A total of 183 patients with craniopharyngioma were enrolled and seven injury types of the HPA were summarized. Relative to intact HPA, exclusive hypothalamus injury significantly increased the risk of anterior (OR, 194.174; 95% CI, 21.311-1769.253; p<0.001) and posterior pituitary dysfunction (OR, 31.393; 95% CI, 6.319-155.964; p<0.001) 1 year after surgery, while exclusively sacrificing stalk infiltrated by tumors didn’t significantly increase the risk of anterior (OR, 5.633; 95% CI, 0.753-42.133; P= 0.092) and posterior pituitary dysfunction (OR, 1.580; 95% CI, 0.257-9.707; P= 0.621) 1 year after surgery. In the training group, the AUCs of nomograms predicting anterior and posterior pituitary dysfunction 1year after surgery were 0.921 and 0.885, respectively, compared with 0.921 and 0.880 in the validation group. Conclusions Intact hypothalamus structure is critical in maintaining pituitary function. Moreover, our preliminary study suggests that the pituitary stalk infiltrated by craniopharyngioma could be sacrificed to achieve radical resection, without substantially rendering significantly worse endocrinological efficiency 1 year after surgery. The user-friendly nomograms can be used to predict hypopituitarism 1 year after surgery.